2019
DOI: 10.1136/bcr-2018-228759
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral arteriovenous malformations during pregnancy: a management dilemma

Abstract: The rupture of a brain cranial arteriovenous malformation (bAVM) has been associated with pregnancy; however, due to scarcity of data about this rare condition, management still remains a dilemma both for obstetricians and neurophysicians. The management plan is decided after weighing the benefits of bAVM treatment against the risk of bleeding in pregnancy. There is consensus on deciding the treatment of ruptured brain AVM during pregnancy based on neurological and not obstetrical indications. The management i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…[3] Maternal physiological changes during pregnancy, such as increased cardiac output and elevated estrogen levels, can affect the structures of these blood vessels, thus making them more prone to rupture. [4][5][6] Although cAVM rupture and hemorrhage during pregnancy YJ, YL, and BL contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Maternal physiological changes during pregnancy, such as increased cardiac output and elevated estrogen levels, can affect the structures of these blood vessels, thus making them more prone to rupture. [4][5][6] Although cAVM rupture and hemorrhage during pregnancy YJ, YL, and BL contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] Maternal physiological changes during pregnancy, such as increased cardiac output and elevated estrogen levels, can affect the structures of these blood vessels, thus making them more prone to rupture. [ 4 6 ] Although cAVM rupture and hemorrhage during pregnancy are rare (0.6–3.5%), [ 7 ] once these events occur, they can be fatal to pregnant women and fetuses. Studies have shown that severe AVM and aneurysm complications during pregnancy account for 5% to 12% of all maternal deaths and 17% of fetal mortality.…”
Section: Introductionmentioning
confidence: 99%